Smallholder soybean farmers supply response in northern Nigeria - Ojiako, I.A.; Manyong, Victor M.; Ikpi, A. (2008)
The supply response of the smallholder soybean growers was investigation using a sample of 307 farmers randomly-selected from Jive villages in Kaduna and Kano States of Nigeria. Different multivariate functional forms were experimented but the power Junction was chosen because of its obvious unique characteristics. The response of the farmers' marketed surplus is positive and significant to changes in cultivated area, own farm-gate price and physical yield of soybean but negative and significant to changes in price of beans. The degree of responsiveness is elastic for farmland area (1.7), physical yield (1.8) and cross-price of beans (1.6) and inelastic own-price of soybean (0.9). The study the need for promoting commercial rather than subsistence soybean farming and recommends policies capable of fostering increases in yield, more access to farmland, and creating price incentives for farmers since soybean production is market-driven.